Waste engine oils : rerefining and energy recovery - Audibert, François (Elsevier, 2006)
Waste Engine Oils presents a complete description of the field of engine used oils, widely collected in the networks of services-stations and garages. It describes the manufacture of base oils in refineries, and mentions the main additives playing an essential role in the quality of the marketed finished oils. The organization of the different systems of collecting in order to obtain a waste oil regenerable or used as fuel are explained. This book covers the main operations of physical and chemical treatments required in waste oil regeneration by covering the fundamental principles techniques such as vacuum distillation, solvent deasphalting, and ultrafiltration. A wide part is dedicated to applications with the description of about twenty processes. In addition, the book describes several types of energetic valorizations which concern a quite important fraction of the collected oil volume. * Comprehensive approach of the waste oil valorization * Overview of chemical engineering operations applied to waste oil * Objective view of the given information on a subject giving rise to competitiveness between the two routes of volorization.